Formose reaction accelerated in aerosol-OT reverse micelles - Masaoka, Makoto; Michitaka, Tomohiro; Hashidzume, Akihito (Beilstein Journal of Organic Chemistry, 2016)
The formose reaction in reverse micelles of aerosol-OT (AOT), triton X-100 (TX), and hexadecyltrimethylammonium bromide (CTAB) was investigated. Time–conversion data have indicated that the interfacial water layer of AOT reverse micelles is a medium that accelerates formation of glycolaldehyde in the formose reaction. The 13C NMR spectra for the products of the formose reaction using formaldehyde-13C as starting material are indicative of the formation of ethylene glycol as a major product.
Keywords: aerosol-OT; formose reaction; hexadecyltrimethylammonium bromide; interfacial layer; reverse micelles; triton X-100; water pool